An introduction to Internet [videorecording] - Samsel, Michael (Free Range Media/White Rain Production, 1994)
Shows the basic protocols of E-mail, File Transfer Protocol, Telnet as well as the latest Internet tools such as Gopher, World Wide Web, Archie, Veronica and WAIS. The AC tools helps us locate, browse and retrieve information. A demonstration is shown by interviewees and internet users.